The president's shadow [large type] - Patterson, James, 1947-; DiLallo, Richard (Patterson, James, 1947- Shadow thriller, 2025)
One of America's iconic thriller heroes recruits his lasting love, Margo Lane, and his great-great-granddaughter, Maddy Gomes, to join an international investigation.